Quasi-Analytical Solutions of DKP Equation under the Deng-Fan Interaction - S. Hassanabadi; A. A. Rajabi; B. H. Yazarloo; S. Zarrinkamar; H. Hassanabadi (Advances in High Energy Physics)
Quasianalytical solutions of Duffin-Kemmer-Petiau equation under scalar and vector Deng-Fan potentials are reported via a novel ansatz.